Requirements engineering for Internet of Things : 4th Asia-Pacific Symposium, APRES 2017, Melaka, Malaysia, November 9-10, 2017, Proceedings /: 4th Asia-Pacific Symposium, APRES 2017, Melaka, Malaysia, November 9-10, 2017, Proceedings. (2018) - Unknown
No abstract available